DAMPAK PERTUMBUHAN EKONOMI TERHADAP PROFITABILITAS BPR SYARIAH DI INDONESIA TIMUR - Sutikno, Aditya Bagas Permana; Al Muizzuddin Fazaalloh (Islamic Economics and finance in Focus, 2024)
The purpose of this research is to examine the impact of economic growth on the profitability of Islamic Rural Banks (BPR Syariah) in East Indonesia, as well as how the profitability of BPR Syariah in East Indonesia is influenced by internal banking variables. This study uses a quantitative method conducted on BPR Syariah in the East Indonesia region, including Sulawesi, Maluku, NTT, NTB, and Papua. A total of 10 BPRs are the subjects of this research. Data collection is carried out using purposive sampling method, using data registered with the Financial Services Authority (OJK) from 2012 to 2022. The data processing technique in this study uses panel data analysis with the assistance of STATA 15. The variables used in this study are divided into two categories, namely dependent and independent variables. The dependent variable used is bank profitability, proxied by Return on Assets (ROA). Meanwhile, the independent variables used include Gross Regional Domestic Product (PDRB), Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Expenses to Operating Income (BOPO). The results obtained in this study indicate that economic growth, represented by the PDRB value, has a significant negative impact on bank profitability. Meanwhile, other internal banking variables have varying effects on bank profitability.